Consumer Acceptance Of Online Banking In Malaysia - Chong, Mun Wei (2006)
The objective of this study was to increase the current understanding of the factors that influence online banking acceptance. More precisely, online banking acceptance was studied from the information systems acceptance point of view referring to the idea that consumers are using banks information system directly and hence more knowledge on the factors that affect information system adoption was needed in order to better undertsand and facilitate the acceptance.